Identifying Enablers and Barriers of Palliative Care Learning in Undergraduate Nursing Education: Systematic Narrative Review - Agustina, Hana Rizmadewi; Rochmawati, Erna Rochmawati; Ala, Muhamad Zulfatul; Fitri, Siti Ulfah Rifaatul; Esoh, Nahyeni Bassah; Karisa, Putri Karisa; Fauziah, Oktaviani Fauziah; Chyntia, Meideline Chyntia (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction: The development of a structured curriculum, relevant teaching and learning methods, and support facilities and access is necessary to improve palliative care education by preparing nursing students as future professional nurses in the palliative care area. This review aims to synthesize available literature explaining the barriers and enablers in implementing palliative care education in undergraduate nursing students.Method: This review uses a systematic narrative review approach. Studies were identified from the PubMed, Scopus, CINAHL, and ProQuest Nursing databases from January 2012 to August 2022 and then selected based on the inclusion criteria that had been set.Results: The search results found that 23 of 890 studies were included. The findings were grouped into obstacles and enablers in four parts, namely curriculum and learning strategies, personal and professional competencies, relationships and enablers, and facilities and access.Conclusions: Identifying barriers and enablers can help educational institutions to provide palliative care education according to the needs and expected developments in clinical practice. Collaboration and cooperation between stakeholders must be increased effectively to help provide maximum education.Keywordsbarriers, enablers, nursing students, palliative care education, undergraduate student